Species limits and morphometric and environmental variation within the South Andean and Patagonian Mulinum spinosum species-group (Apiaceae-Azorelloideae). Issue 5 (3rd September 2017) - Fernández, Martina; Ezcurra, Cecilia; Calviño, Carolina I.
Abstract : Delimiting species is an important, but frequently difficult aspect of systematics that should be addressed using data from multiple sources. Here we combine morphometric analyses and environmental characteristics to delimit species in the South Andean and Patagonian taxonomically difficult species-group composed by Mulinum spinosum, M. echinus and M. leptacanthum (Apiaceae-Azorelloideae). Molecular phylogenies have shown that these three species form part of a polytomy together with other Mulinum species, and therefore these data are not useful for their delimitation. We include measurements of 25 morphometric variables from 163 herbarium specimens and perform univariate and multivariate principal component analysis (PCA) and discriminant analysis (DA) to establish the limits amongst the three mostly sympatric, morphologically similar, and phylogenetically unresolved species. We also use 19 bioclimatic and three geographic variables from localities of the specimens to infer environmental characteristics of the taxa and test their relation with morphological variation. Morphological evidence supports the inclusion of M. echinus within the morphologically and climatically variable M. spinosum, and rejects its recognition as a distinct taxon at any rank. On the contrary, M. leptacanthum is considered a morphologically distinct species, generally restricted to high altitude areas of the southern Andes with a cooler and wetter climate. Within the widespread M. spinosum, environmental gradients of precipitation and temperature relate to morphological gradients (e.g., in leaf and inflorescence sizes, in leaf acicularity, and in fruit-wing width). These last results showed that the large morphological variation in vegetative and reproductive characteristics of this species that grows in arid and semiarid habitats are related to regional climatic gradients that have probably been important in the evolution of this species' plasticity, diversification, and differentiation.